ANALISIS PENDAPATAN PEDAGANG DI PASAR KEDIRI KECAMATAN KEDIRI KABUPATEN TABANAN DITINJAU DARI FAKTOR INTERNAL - NGURAH WISNU MURTHI (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this study was to determine the influence of internal factors on the income of traders in Kediri Market, Kediri District, Tabanan Regency. The internal factors to be examined are capital and length of business. The research was conducted at the Kediri Market, Kediri District, Tabanan Regency, where the object of research was traders at the Kediri Market. The number of samples is 65 respondents. The method used in this research is Proportionate Stratified Random Sampling. Data collection was carried out using questionnaires, observation and documentation. The data analysis techniques used to solve the problems in this study are: 1) Classical Assumption Test which includes: Normality Test, Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test, 2) Hypothesis Test with Multiple Linear Regression Analysis Techniques.Based on the results of the analysis it is known that with a confidence level of 60.3 percent, all independent variables have an effect either simultaneously or partially on the dependent variable. This means that internal factors consisting of capital and length of business affect the income of traders in the Kediri Market both simultaneously and partially. When viewed from the coefficient of determination, only 60.3 percent of the variation in capital, length of business can explain the variation in the income of traders at the Kediri Market, Kediri District, Tabanan Regency. This is because there are many other factors that affect the income of both internal and external traders that are not discussed in this study.